2016
DOI: 10.1111/tan.12907
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA alleles and haplotypes with CYP21A2 gene p. V282L mutation in the Croatian population

Abstract: The CYP21A2 mutations that are in linkage disequilibrium with particular HLA-A, -B, -DRB1 alleles/haplotypes, cause deficiency of the 21-hydroxylase enzyme (21-OHD) and account for the majority of congenital adrenal hyperplasia (CAH) cases. The aim of this study was to investigate those associations with the p.V282L mutation linked to the non-classical (NC) form of CAH among Croatians. The study included parents of patients with the NC form of CAH, positive for the p.V282L mutation (N = 55) and cadaveric donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The linkage between AH 65.1 and CYP21A2 gene p.V281L, observed in F1 and F2, is included in the conserved extended MHC haplotypes 65.1 described by Dorak and colleagues together with other 36 conserved extended MHC haplotypes. This linkage has been noted in Mediterraneans . In F4‐P1, F16A HLA class I haplotype is linked to CYP21A2 gene p.V281L mutation and also HLA class II haplotype DRB1*03:01‐DQB1*02:01 , which is a MHC extended haplotype recently described for the first time in Croatians .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The linkage between AH 65.1 and CYP21A2 gene p.V281L, observed in F1 and F2, is included in the conserved extended MHC haplotypes 65.1 described by Dorak and colleagues together with other 36 conserved extended MHC haplotypes. This linkage has been noted in Mediterraneans . In F4‐P1, F16A HLA class I haplotype is linked to CYP21A2 gene p.V281L mutation and also HLA class II haplotype DRB1*03:01‐DQB1*02:01 , which is a MHC extended haplotype recently described for the first time in Croatians .…”
Section: Discussionmentioning
confidence: 57%
“…This linkage has been noted in Mediterraneans . In F4‐P1, F16A HLA class I haplotype is linked to CYP21A2 gene p.V281L mutation and also HLA class II haplotype DRB1*03:01‐DQB1*02:01 , which is a MHC extended haplotype recently described for the first time in Croatians . No previous data have been found about the linkage of F16A, V281L mutation and HLA‐DRB1*04:02‐DQB1*03:02, which is present in F3.…”
Section: Discussionmentioning
confidence: 91%
“…Historically, the HLA-B*14 allele was found to be in genetic linkage disequilibrium with nonclassic CAH in a population of Ashkenazi Jews, Hispanics, and Italians (Speiser et al, 1985). Later studies confirmed an association between p.V281L, and the HLA-B*14 allele in Ashkenazi Jews, non-Ashkenazi Jews, Croatians, and Turks (Yarman et al, 2004; Israel et al, 2006; Grubic et al, 2016). In accordance with these findings, we found an association between p.V281L and the extended haplotype HLA-B*14-C*08 in our ethnically diverse population of CAH patients.…”
Section: Discussionmentioning
confidence: 91%
“…Following the discovery of the CYP21A2 gene on chromosome 6p21.3 within the HLA complex in 1985, some studies have found associations between specific CYP21A2 mutations and HLA types. The strongest finding to date has been the association between the commonly found p.V281L nonclassic CAH mutation and HLA-B*14 (Speiser et al, 1985; Israel et al, 2006; Grubic et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation